Mineral composition and secondary metabolites in the leaves of Lophira lanceolata (Ochnaceae) from Bondo City in the Democratic Republic of the Congo - Baka Zawa, Aziza; Upoki , Dieudonné Agenonga; Tebandite, Emmanuel Kasayi; Mbinze , Jérémie Kindenge; Marini Djang'eing'a, Roland (Orapuh Journal, 2025)
IntroductionMany nutrient-rich plants remain underutilised in the diets of sub-Saharan populations, particularly in the Bondo area of northern Democratic Republic of Congo (DRC). It is therefore necessary to valorise them through appropriate laboratory investigations.Purpose This study focused on Lophira lanceolata to investigate the phytochemical composition and mineral content of its leaves.Method Standard chemical screening and atomic absorption spectrometry were employed to assess phytochemical composition and mineral content, respectively.Results Leaves were collected approximately 54 km from Bondo City. Phytochemical screening revealed flavonoids (flavones) at 12.7 ± 0.31%, terpenes at 2.49 ± 0.23%, saponins at 0.65 ± 0.02%, and sterols at 0.60 ± 0.05%. Gallic tannins and alkaloids were detected but not quantified. The loss on drying was 10.70 ± 0.35% and the total ash content was 5.90 ± 0.11%. Mineral analysis indicated high concentrations of iron (15.63 ± 0.15%), sulfur (13.85 ± 0.11%), and silicon (5.25 ± 0.02%), along with moderate levels of zinc (3.47 ± 0.56%), calcium (2.68 ± 0.01%), potassium (1.89 ± 0.04%), phosphorus (0.80 ± 0.001%), copper (0.61 ± 0.02%), and trace titanium (<0.24%). The calcium-to-phosphorus ratio (3.35) suggests potential use in livestock nutrition, particularly during the dry season.Conclusion Our findings demonstrate that Lophira lanceolata leaves from Bondo are a rich source of bioactive compounds and essential minerals, supporting their traditional use against anaemia, infections, hypertension, and inflammatory conditions. The presence of silicon and sulfur suggests additional benefits for bone health, dermatological conditions, and pest resistance. These results highlight the plant’s potential applications in phytotherapy, veterinary medicine, and agro-nutrition.